Enhancing radon detection accuracy with charcoal canister: A simple method for measuring radon - Kim, Min Jun; Jang, Won Jun; Cho, Seung Yeon; Shim, Jae Oh (Radiation Measurements, 2024)
Charcoal canisters are widely used devices for measuring radon concentration in the atmosphere, but they are sensitive to humidity. A newly designed super absorbent polymer (SAP) filter was applied to charcoal canisters to enhance their resistance to ambient humidity, thereby improving the accuracy of radon concentration measurements. The charcoal canister with the SAP filter had an error of approximately 1.3–2.6% compared to the reference value (measured by RAD7), whereas the charcoal canister without the SAP filter exhibited an error of 12–18% compared to the reference value. Additionally, the charcoal canister with the SAP filter demonstrated over 90% of response value even under very high relative humidity conditions of 90%, indicating strong resistance to ambient humidity.
Keywords: Ambient humidity; Charcoal canister; Detection accuracy; Polymer filters; Radon concentrations; Radon detection; Reference values; SIMPLE method; Super absorbent polymer; Superabsorbent polymer; Charcoal canisters; humidity; Radon; Super Absorbent Polymer (sap)